1980
DOI: 10.1159/000145270
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic visualization of various morphological types of collagenous fibres

Abstract: The connective tissue fibres of various parts of different fascial and aponeurotic planes of the ventral abdominal walls of 26 albino rats were examined with the scanning electron microscope. Five types of collagen fibres could be identified and visualized stereo-scopically: (1) the fine network seen around the muscle fibres; (2) the loose collagenous bundles and their investing reticular network in the deep fasciae; (3) the wavy parallel bundles in the free part of the aponeuroses; (4) the dense mature collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Fine collagen fibrils with a banding pattern are formed at an early stage of collagen fibril formation in vivo, developmentally, or during the initial stage of wound healing (Rizk 1980;Craig and Parry 1981). During wound healing, the fibrils are stained with anti-type V collagen antibody, but type I collagen is rarely found in the fibrils (Betz 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Fine collagen fibrils with a banding pattern are formed at an early stage of collagen fibril formation in vivo, developmentally, or during the initial stage of wound healing (Rizk 1980;Craig and Parry 1981). During wound healing, the fibrils are stained with anti-type V collagen antibody, but type I collagen is rarely found in the fibrils (Betz 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The dif ference of properties suggests that human masseter muscles contribute to a large part to the function of jaw movements with other masticatory muscles. Rizk [9] reported that a delicate reticulum network of very fine fibers filled the space of large parallel collagen bundles of the aponeurosis in the ventral abdominal wall of the rat. In our results, these irregular collagen fibers were not found among the colla gen bundles, but a few elastic fibers were found in the superficial and middle portions of tendon in masseter mus cles at an ultrastructure level.…”
Section: Discussionmentioning
confidence: 99%
“…In general, collagenous fibrils of connective tissues can be classified into two types: large, straight parallel fibrils (Fawcett, 1986); and helically arranged, wavy fibrils that form sinuous bundles or threedimensional sheaths (Rizk, 1980). The connective tissues are composed of type I, type III, and type V which indicate intermixed fibrils by chemical and immunohistochemical methods (Light and Champion, 1984;Mayne and Sanderson, 1985).…”
Section: Discussionmentioning
confidence: 99%